(untitled) (Journal of Legal Studies, 2015)
The passing of the new codes was justified by the legislator by taking into account both the comparative law in the field, as well as the social and economic realities, the evolution of the doctrine and jurisprudence, the need for readjusting the punitive treatment within the normal limits, the simplification of the incriminatory texts and the need to avoid the overlapping of various criminal provisions. The current paper aims to analyze the offenses against the justice process, which have come to know new nuances in the current penal configuration, being distinctively specified in Title IV of the Penal Code‟s Special Part; the syntagm "Crimes hindering justice" has been replaced with "Crimes against the carrying out of justice", since these crimes have not always effectively prevented justice from being carried out; sometimes they only posed a threat to the justice process. The changes regarding these offenses were justified by the legislator by invoking the need to ensure the legality, impartiality, independence and unwavering nature when carrying out the justice process, new incriminations being brought up and other criminal acts being rethought, which were already criminalized by the previous legislation.